Islam and humanity consequences of a contemporary reading - Shahrour, Muhammad (Islamic studies at Gerlach Press, 2018)
This book by Mohammed Shahrour is about the implications of a contemporary reading of the Qur'an. "We must re-examine the prior reading of religion and introduce Islam from its original source, the authoritative revelation, on the basis of a contemporary reading that takes into account the level of knowledge of the 21st century and the scientific and ethical development that have been achieved.